Analisis Pengaruh Penerimaan Pajak Parkir Guna Meningkatkan Pendapatan Asli Daerah Di Badan Pendapatan Daerah Kota Medan - Mhd. Arifta Pulung Tumannger; Wahyu Syarvina (Universitas 45 Surabaya, 2024)
Research conducted at the Medan City Regional Revenue Agency. The aim of this research is to understand and analyze how the level of realization of parker rent increases the number of Indigenous Regional Residents (PAD) in the Regional Revenue Agency of Medan City. To understand and analyze why the parking revenue target at the Medan City Regional Revenue Agency has not been met. To understand and analyze why taxpayer rates in the Medan Regional Revenue are still not optimal. The research method used here is called the Qualitative method which produces interview results. The contribution of parking to the Medan Raya Regional Development Agency's PAD is relatively low. This results in the tax and levy management body not achieving the expected goals and being ineffective where the cause of the realization of the parking tax lies. Many people are reluctant to share their honest parking tax income. This is in accordance with research findings (Jufrizen, 2013) which state that research data shows that the area received from the parking levy subsector has not reached the optimal level. This is because the target and realization period do not always align, so further research is needed to find out what can be done to increase the area of ​​revenue from the parking levy subsector more effectively.